GAMBARAN TINGKAT STRES DAN NYERI KEPALA PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA - CUT INTAN MUTIA SASTRA; IRFAN HAMDANI (LP2MTBM MAKARIOZ, 2023)
A person's mental health is a condition that is considered well-being, that is, someone who has prosperous mental health will be able to face and overcome various stresses in normal life. At the University of Gondar in Ethiopia, there are mental disorders that occur in students, especially medical students, symptoms can include psychological pressure such as anxiety and depression. This is caused by additional stress on medical students due to the long-term learning period so they are at risk of exposure to symptoms such as headaches. The aim of this research was to determine the level of stress and headaches of students at the Faculty of Medicine, Muhammadiyah University of North Sumatra with a sample of 80 students from the class of 2020 and class of 2018. Samples were taken using quota sampling technique. with a cross sectional research design. Sampling using. From the results of the research above, it was found that the number of FK UMSU students class of 2018 and class of 2020 who were respondents based on stress levels was 55 people (68.8%) normal, 9 people (11.3%) mildly stressed, 13 people (16.3%) %) moderate stress, and 3 people (3.8%) had severe stress. Meanwhile, for the degree of headache, it was found that the number of FK UMSU students from the class of 2018 and class of 2020 based on the degree of headache was 7 people (8.8%) never, 30 people (37.5%) headaches did not interfere with daily activities, 31 people (38.8%) had headaches that interfered with daily activities (still working but were disturbed), and 12 people (15.0%) had headaches and needed rest (unable to work) for a total of 80 people (100.0% )